THE ROLE OF HIGHER EDUCATION INSTITUTION LEADERS IN BUILDING HUMAN CAPITAL IN CAMBODIA: CHALLENGES AND STRATEGIES - In, Channdy (jfpublisher, 2025)
Cambodia envisions to becoming an upper-middle-income country by 2050 and a high-income country by 2050. It needs to invest in its human capital to achieve such a vision. This study aims to examine the roles and competencies for higher education institution (HEI) leaders to best prepare Cambodian graduates to contribute to achieving Cambodia’s development vision. It also aims to identify key challenges faced by HEI leaders and appropriate strategies to help them prepare Cambodian graduates to be qualified human capital. The study employed a Delphi method, with a focus on qualitative data. A total of 57 participants (panelists) who were educational leaders, senior academics, and doctoral students participated in the study. The findings showed several key roles that Cambodian HEI leaders need to play and a number of competencies they need to possess in order to serve their roles effectively and make a difference to Cambodian higher education. Several key challenges faced by HEI leaders were also identified. The study also revealed a number of strategies that should be adopted for HEI leaders to best prepare Cambodian graduates for the world of work and enable them to be able to meaningfully contribute to achieving Cambodia’s development vision. This study concludes with implications for policy and research.